“Acqua minerale” cioè come tradurre i giochi di parole di Achille Campanile - Słapek, Daniel (Romanica Silesiana)
Achille Campanile remains one of the greatest humorists of the twentieth century and he is generally deemed the precursor of the Theatre of the Absurd. According to Umberto Eco, Campanile’s theatre allows us to learn all the mechanisms of humour. Wordplay is arguably the author’s favourite device; it is a device by means of which he gives a humorous tone to his texts. In the case of one-act plays and “in due battute” tragedies, wordplay frequently determines the structure of the entire text. The article attempts to evaluate the translations of those of Achille Campanile’s texts which are thoroughly based on wordplay. The author tries to discover the criterion of evaluating similar texts on the example of the tragedy Acqua minerale. That is why he evokes the premises of the cognitive theory of translation by E. Tabakowska and K. Hejwowski, as well as J. Henry’s classification of wordplay translation. Extending the classification of the latter is suggested, since arguably another criterion, that of cognitively conceived scene/scripts, should be added. The article demonstrates the groundlessness of the thesis that wordplay is untranslatable. During the process of translation the translator does not work withe words, but with scenes and scripts, and the preservation of those constitutes the basic criterion of translating the texts in question. Key words: Achille Campanile, wordplay, translation, scene, scripts.